PENGARUH BELANJA INFRASTRUKTUR PEMERINTAH TERHADAP KAPITALISASI PASAR KELOMPOK INDUSTRI INFRASTRUKTUR, UTILITAS DAN TRANSPORTASI PADA PERUSAHAAN YANG TERDAFTAR DALAM BURSA EFEK INDONESIA (STUDI DATA TIME SERIES 2005-2014) - L Suparto LM (MAKSI, 2015)
This research aims to determine the effect of government infrastructure expenditureto market capitalization infrastructure, utilities and transportation industry of listedcompanies in the Indonesian Stock Exchange (IDX) during 2005-2014. Research analysisusing descriptive and verification. Data used is time series data as realization of directexpenditures of government in infrastructure sector which consists of transportation andcommunication. Market capitalization data is capitalization of industry groupinfrastructure, utility and transportation companies listed on the Indonesian StockExchange (IDX) during 2005-2014. Analysis data used descriptive and verification.Descriptive analysis is used to describe the research variables development. Theverification analysis used to examine the effect between variables with include theselection models test, specifications model test, normality test, regression test, coefficientdetermination test, statistical t and f test.The result analysis showed government infrastructure expenditure variables ispositive and significant impact on the market capitalization of the infrastructure, utilitiesand transportation industry listed companies in the Indonesian Stock Exchange during2005-2014, with the determination level of 47.47% and the remaining 53.52% is explainedby other variables that are not described or include in the research models function suchas National income, inflation, exchange rates and others. One of suggestions in thisreseach is central government should be consistent on each target and developmentactivities that have been assigned in infrastructure expenditure every year. It is importantto do, so the financing gap does not encourage inflation that couse high cost in theproduction process due to the inflation of infrastructurecommodity. In addition, effectivecontrol efforts to development process is being carried out and also continue by synergyamong the stakeholders that being implementation process development is done on time, aswell as efforts to establish strategic policies and legal certainty for investors. So theinvestment climate more conducive to attracting private investors invest in theinfrastructure, utilities and transportation sector in the Indonesian Stock Exchange.Keywords :Market Capitalization, Infrastructure, Utilities and Transportation Industry,Government Infrastructure Expenditure, Indonesian Stock Exchange.